Analisis Customer In Service Comunication Pada Peningkatan Minat Menabung (Studi Pada Nasabah Bank BNI) - Nurhaedah Nurhaedah (MBIA, 2019)
The purpose of this study is to analyze the relationship between the people , process and physical evidence strategies on increasing customer interest in saving. Determination of the number of samples based on the area of ​​residence of the customer in the area of ​​Makassar City. With the quantitative approach method and the analytical tool using multiple linear regression, the SPSS program. From the results of the study prove that the interest of customers to save simultaneously is influenced by the strategy of people , process and physical evidence . The research can provide evidence that there is a link between management theory and policy that breaks down in conclusions. This study has limitations so that it can make a reference for future researchers.